A step in the right direction? Change in mental well-being and self-reported work performance among physically inactive university employees during a walking intervention - Thøgersen-Ntoumani, Cecilie; Loughren, E.; Taylor, I.; Duda, J.; Fox, K. (Elsevier BV, 2014)
Objective: To examine well-being and work performance changes accompanying participation in a 16-week uncontrolled feasibility lunchtime walking trial. Method: Participants were 75 (92% female; M age ¼ 47.68) previously physically inactive non-academic employees from a large British university. Multilevel modelling analyses examined well-being and work performance trajectories from baseline to post-intervention, to four months later, controlling for group membership and trait affectivity. Results: Increases in perceptions of health, subjective vitality, and work performance, and decreases in fatigue at work were observed. Changes were sustained four months after the end of the intervention. No changes were identified for enthusiasm, nervousness and relaxation at work. Conclusion: Although this was a relatively small uncontrolled feasibility trial, the results suggest that participation in a walking programme may be associated with sustainable well-being benefits and improvements in perceptions of work performance.